Ending War, Building Peace : Contribution of the National DDR Program in DRC to Peace in the African Great Lakes Region - Conoir, Yvan (World Bank, Washington, DC, 2017)
The National Disarmament, Demobilization and Reintegration Program (NDDRP) in the Democratic Republic of the Congo (DRC) was implemented over a period of seven years (2004- 2011) with the World Bank's support and funding. The NDDRP had three objectives: 1) disarmament of all combatants willing to be granted a status of demobilized person; 2) demobilization of all ex-combatants who met the conditions for a return to civilian life through a downsizing process of armed forces or groups; and 3) reintegrate the demobilized in the social and economic practices of the community of their choice with opportunities and conditions similar to those of other members of the community. To achieve these objectives, the DRC government initially established a National Commission of Demobilization and Reinsertion (CONADER, 2003), then established the NDDRP (2004), and finally created a new NDDRP Implementation Unit (IU-NDDRP, 2007). NDDRP was divided into three distinct phases, each capitalizing on the gains as well as the mistakes of the past. Economic reintegration of demobilized ex-combatants represented four out of five demobilized as recorded by the program. At the program's conclusion, the implementing partners decided to support the creation, legalization, and strengthening of demobilized persons' economic associations. This model of economic and social reintegration developed by the NDDRP can serve as a model framework for future rehabilitation and reintegration processes in DRC as well as in other countries. Finally, as the results were not as high as expected in regard to the number of women as well as wounded and disabled veterans demobilized, the NDDRP can be lauded for successfully reaching and reintegrating a highly significant number of Children Associated to Armed Forces and Groups (CAAFG) through special projects executed by different implementing partners.